2013
DOI: 10.1093/jac/dkt304
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of piperacillin and tazobactam in critically ill patients undergoing continuous renal replacement therapy: application to pharmacokinetic/pharmacodynamic analysis

Abstract: Population pharmacokinetic models have been developed and validated for piperacillin and tazobactam. Based on the pharmacokinetic/pharmacodynamic analysis, dosing recommendations are given considering the residual renal function of the patient and the MIC for the isolated bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 29 publications
8
44
3
Order By: Relevance
“…Normally, exposure of antimicrobials that are eliminated mainly in urine, such as cephalosporins, is higher in patients with renal insufficiency than in patients with normal renal function [26,27] and therefore the probability to reach the pharmacodynamic target significantly increases. This means that patients with normal renal function have more risk of underdosage.…”
Section: Organismmentioning
confidence: 99%
“…Normally, exposure of antimicrobials that are eliminated mainly in urine, such as cephalosporins, is higher in patients with renal insufficiency than in patients with normal renal function [26,27] and therefore the probability to reach the pharmacodynamic target significantly increases. This means that patients with normal renal function have more risk of underdosage.…”
Section: Organismmentioning
confidence: 99%
“…In this context, CRRT represents a particular challenge in terms of dosing, especially for hydrophilic antibiotics, as concentrations may vary depending on the degree of extraction, which in turn depends on the CRRT modality, on drug physicochemistry and, presumably, on CRRT intensity [7]. Moreover, residual renal function is usually variable, difficult to assess and rarely considered when dosing, despite its relevant contribution to antibiotic CL in patients undergoing CRRT that has been described for meropenem and piperacillin among others [26,29,32]. Finally, the patient’s condition evolves throughout the ICU stay so the influence of the previously mentioned factors may vary over time, making it difficult to generalize recommendations only based on CRRT modality and intensity.…”
Section: Effect Of Septic Shock and Crrt In Antibiotic Dosing Optimizmentioning
confidence: 99%
“…Other studies include septic and polytrauma patients requiring CRRT [25,32]. Of note, one of these studies overcame the admission diagnosis-driven variability by developing a population pharmacokinetics model.…”
Section: Main Limitations Of Available Pharmacokinetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous piperacillin pharmacokinetic studies have been conducted in critically ill patients concurrently treated with variable modes and doses of continuous RRT (CRRT) [9][10][11][12][13][14][15][16], none have evaluated CI administration. The only related paper was based on simulation and it concluded that CI administration of piperacillin could be beneficial in this context [17]. Therefore, evaluating the use of CI of piperacillin during CRRT will inform ICU clinicians regarding its application.…”
Section: Introductionmentioning
confidence: 99%